A cost-effective and powerful climate policy: pioneers pave the way - Bråten, Jan (Bergen, 2015)
"The climate problem requires changes in every country and across almost all sectors. For us to have a realistic chance at limiting global warming to 2°C, emissions must be cut by around 60% between 2014 and 2050, and towards the end of this century, greenhouse gas emissions need to be close to zero. At the same time, the global population is expected to grow by more than 40% towards the year 2100, and world production of goods and services may increase eightfold (given annual economic growth of 2.5%). Today’s economy is built on the use of fossil energy, which is also the biggest source of global warming. Future growth and prosperity need to be built on different energy solutions altogether. In the European Commission’s Energy Roadmap 2050, the power sector has almost zero emissions in 2050. In order to reach such goals, pervasive restructuring of energy production and consumption is required. There is also a need for changes within transport, in parts of agriculture and manufacturing, and in how we plan and build the society of tomorrow. To efficiently promote changes such as these, we need new and better technologies, new ways of organising institutions and sectors, and not least, new ways of thinking."